Orientation-dependent Dxz4 contacts shape the 3D structure of the inactive X chromosome - G. Bonora (Nature Portfolio, 2018)
The inactive X chromosome condenses into a bipartite structure. Here the authors use cells with allelic deletions or inversions to show that the Dxz4 locus is necessary to maintain the bipartite structure and that Dxz4 orientation controls the distribution of contacts on the inactive X chromosome.